Evaluation of Online Learning at SDIT Adzkia 2 Sukabumi - Sofiawati, Esmi Tsalsa; Ratnasari; Aonudin, Asep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This study aims to describe the achievements of online learning programs in Semester Odd Academic Year 2020/2021 at SDIT Adzkia 2 Sukabumi. This study uses the CIPP model (Context, Input, Process, and Product) as an evaluation tool. The method used in this study is research-evaluation with a descriptive-evaluative approach. The data collection in this evaluation research is observation, interviews, and documentation studies. Data analysis techniques used in this research are data collection, data reduction, data presentation, and drawing conclusions. Sources of data obtained from school principals, teachers and homeroom teachers, TU staff and curriculum staff. The results showed that the online learning program at SDIT Adzkia 2 Sukabumi had achieved good results in its implementation. This can be seen from the suitability of the indicators assessed with the 4 components of the CIPP evaluation, namely in the context component there is a legal basis and purpose for implementing the program, in the input component, there are human resources, targets and infrastructure in program implementation, the process component contains the planning process, program socialization and monitoring process, on the product component there is a report on program results and the achievement of program objectives. Overall, the implementation of the online learning program at SDIT Adzkia 2 Sukabumi can be said to have been effective because it has met the standard criteria that have been determined. However, there are several focuses that need to be improved including, 1) increasing additional programs to fill the free time of students while studying at home, 2) principals to be more intense in socializing and communicating with students' parents, 3) teachers to provide more variations in learning media.